Immunohistochemical Expression of Bronchial Dysplasia Associate Proteins in Uterine Cervical Lesions [6P]. (May 2016) - Sasa, Hidenori; Suzuki, Ayako; Sei, Kiguna; Shimazaki, Hideyuki; Sugita, Michio; Furuya, Kenichi
Abstract : INTRODUCTION: Bronchial dysplasia associate proteins are involved in the proliferation, cell differentiation and adhesion, tumorigenesis, invasion and metastasis of cancer. We examined the immunohistochemical expression of bronchial dysplasia associate proteins in uterine cervical lesions. METHODS: Specimens from 32 patients with uterine cervical intraepithelial neoplasia (CIN) or uterine cervical invasive carcinoma were immunohistochemically evaluated for the expression of the 6 proteins associated with bronchial dysplasia: serpin peptidase inhibitor B2 (SERPINB2), carboxypeptidase A4 (CPA4), keratin 6A and 13, interleukin 1 receptor antagonist (IL-1Ra), small proline-rich protein 3 (SPRR3) and desmoglein 3 (Dsg3). Immunohistochemistry staining intensity was quantitatively scored from 0 to 2+. This study was approved by the Institutional Review Board. RESULTS: The positive expression rates of SERPINB2, CPA4, Dsg3 and SPRR3 were 84%, 62.5%, 27%, and 18.9% in the uterine cervical cells, 87.5%, 75%, 70.3%, and 0% in the biopsy tissue specimens, respectively. The expression of keratin6A/13 was not specific, and the expression of IL-1Ra only in the cervical dysplastic cells revealed positive, but negative in normal cells and cervical invasive carcinoma cells, and in all biopsy tissues. The expression of SERPINB2 seemed to have positive correlation with the progression of lesions, but the expression of CPA4 in only the dysplastic cells revealed positive. CONCLUSION: SERPINB2 might be useful as a marker for uterine cervical lesions because it was expressed according to the grade of the CIN and cervical invasive carcinoma specimens. CPA4, Dsg3, and IL-1Ra could be potential immunohistochemical markers for uterine cervical lesions because of positive expression in the dysplastic cells.